Waterproof material for electronic products and preparation method thereof

By spraying nanocoatings with organic inorganic hybrid nanoresin and silica microspheres on the surface of electronic products, the corrosion and deformation problems of electronic products when encountering water is solved, and excellent waterproof and corrosion resistance are achieved, while reducing environmental protection. and security risks.

CN119192888AInactive Publication Date: 2024-12-27深圳市兴威格科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598999.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The waterproof materials of existing electronic products are prone to corrosion and deformation when exposed to water, resulting in electrical failure. The existing waterproofing treatment methods have problems such as poor heat dissipation, high rework cost and the use of volatile solvents.

Method used

Using a nanocoating including organic and inorganic hybrid nanoresin, silica microspheres, isopropanol and platinum catalyst, mixed under nitrogen protection and heated treatment, the nanocoating is formed and sprayed on the surface of electronic products and baked and dried to form an optimization waterproof material.

Benefits of technology

It realizes environmentally friendly and safe water-based waterproof materials, improves intermolecular force and hydrophobicity, enhances the waterproof and corrosion resistance of electronic products, and does not affect the normal conductivity of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of waterproof materials, and particularly discloses a waterproof material for an electronic product and a preparation method of the waterproof material. The preparation method comprises the following steps: S1, mixing a composite modifier, silicon dioxide sol and water under the protection of nitrogen, heating to 75-80 DEG C, adding nitric acid, keeping the temperature for 6-8 hours, and discharging to obtain organic-inorganic hybrid nano resin; s2, taking the organic-inorganic hybrid nano resin, silicon dioxide microspheres, silicon dioxide, isopropanol, water and a platinum catalyst, and stirring at a high speed to obtain a nano coating; spraying to the surface of an electronic product, baking at 70-80 DEG C for 2-3 hours, and drying to obtain a waterproof material; the organic-inorganic hybrid nano resin comprises the following raw materials in parts by mass: 8-10 parts of a composite modifier, 4-6 parts of silicon dioxide sol, 80-100 parts of water and 0.5-0.8 part of 1M nitric acid, the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1: (1-2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof materials, and specifically discloses a waterproof material for electronic products and a preparation method thereof. Background Art

[0002] At present, some electronic products may be corroded and deformed when in contact with water during use, resulting in the risk of electrical failure. At present, the waterproof and moisture-proof treatment of electrical equipment includes the following: (1) Structural waterproofing: Isolation from the internal electrical parts through external packaging, but the waterproof effect needs to be improved; (2) Potting waterproofing: Potting glue is used for wrapping, but there are problems such as poor heat dissipation and high repair costs; (3) Surface coating waterproofing: Waterproof coating is applied to the surface of electronic products to prepare waterproof materials. Nano waterproof coating is a hot topic in current research. It has the advantages of small thickness, good hydrophobicity, good heat dissipation performance, and does not affect the normal conductivity of connectors; in order to further improve the life of waterproof materials, the coating needs to have good bonding strength, good corrosion resistance, and good bonding; and for environmental protection considerations, the use of volatile solvents needs to be reduced. Therefore, it is of great significance to study a waterproof material for electronic products and its preparation method. Summary of the invention

[0003] The object of the present invention is to provide a waterproof material for electronic products and a preparation method thereof, so as to solve the problems raised in the prior art.

[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a waterproof material for electronic products, comprising the following steps: S1: Mix the composite modifier, silica sol and water under nitrogen protection, heat to 75-80°C, add nitric acid, keep warm for 6-8h, and discharge to obtain organic-inorganic hybrid nano resin; S2: Take organic-inorganic hybrid nano resin, silica microspheres, silica, isopropanol, water, and platinum catalyst, stir at high speed to obtain nano coating; spray the nano coating onto the surface of the electronic product, bake at 70-80° C. for 2-3 hours, and dry to obtain a waterproof material.

[0005] More optimally, the organic-inorganic hybrid nanoresin includes the following raw materials, calculated by weight: 8 to 10 parts of a composite modifier, 4 to 6 parts of silica sol, 80 to 100 parts of water, and 0.5 to 0.8 parts of 1M nitric acid; the composite modifier includes an epoxy silane coupling agent and a tackifier in a mass ratio of 1:(1 to 2).

[0006] More optimally, the preparation of the tackifier includes the following steps: taking vinyltrimethoxysilane and vinyl-terminated silicone oil, diluting them to a mass concentration of 50% with a mixed solvent (cyclohexane and toluene in a volume ratio of 1:1), adding a platinum catalyst under nitrogen protection, heating to 50-60°C, dropping tetramethylcyclotetrasiloxane diluted to a mass concentration of 50% with cyclohexane, heating to 70-75°C, reacting for 2-3 hours, removing the solvent, and obtaining the tackifier.

[0007] More optimally, the tackifier comprises the following raw materials, calculated by weight: 20-30 parts of vinyltrimethoxysilane, 40-50 parts of vinyl-terminated silicone oil, and 20-30 parts of tetramethylcyclotetrasiloxane.

[0008] More optimally, the viscosity of the vinyl terminated silicone oil is 500-1000 cSt.

[0009] More optimally, the preparation of the silica microspheres includes the following steps: taking hollow mesoporous silica and pentaerythritol triacrylate A, adding them to ethanol and stirring evenly, placing them in a vacuum box with a pressure of -50 kPa for 2 to 3 hours, adding 2,2,3,3,3-pentafluoropropyl acrylate, 2-vinylbenzimidazole, pentaerythritol triacrylate B, and dibenzoyl peroxide, stirring at 75 to 78° C. for 10 to 12 hours under nitrogen protection, and removing the solvent to obtain silica microspheres.

[0010] More optimally, the silica microspheres include the following raw materials, calculated by mass: 10-15 parts of hollow mesoporous silica, 1-2 parts of pentaerythritol triacrylate A, 300-400 parts of ethanol, 0.3-0.5 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.4-0.6 parts of 2-vinylbenzimidazole, 0.2-0.3 parts of pentaerythritol triacrylate B, and 0.01-0.02 parts of dibenzoyl peroxide.

[0011] More optimally, the nano coating comprises the following raw materials, calculated by weight: 10-15 parts of organic-inorganic hybrid nano resin, 1-2 parts of silica microspheres, 0.3-0.5 parts of silica, 1-2 parts of isopropanol, 55-60 parts of water, and 0.005-0.006 parts of platinum catalyst.

[0012] More optimally, the nano coating spray thickness is 1~2μm.

[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: a nano coating is sprayed on the surface of an electronic product to obtain a waterproof material; the raw materials of the nano coating include organic-inorganic hybrid nano resin, silica microspheres, silica, isopropanol, water, and a platinum catalyst; it belongs to a water-based system, is environmentally friendly and safe, has a small thickness, and does not affect the performance of electronic products; A composite modifier is introduced into the organic-inorganic hybrid nano resin, and a polar group is introduced to improve the intermolecular force; the tackifier in the composite modifier is based on tetramethylcyclotetrasiloxane, and vinyl trimethoxysilane that can be combined with silica sol and vinyl-terminated silicone oil with a viscosity of 500-1000 cSt are introduced; the long chain of silicone oil has good hydrophobicity, and can increase the viscosity of the system, and increase the bonding force between the coating and the surface of the electronic product; the viscosity of the silicone oil should not be too high, otherwise it will affect the fluidity of the coating, making it difficult to apply and uneven coating; too low viscosity leads to insufficient hydrophobicity, and the short chain segment is not easy to spread on the surface of the substrate; when preparing the tackifier, the amount of each raw material added is controlled, so that the tackifier still has silicon hydrogen groups, which can participate in the reaction with the double bonds in the silica microspheres in the subsequent steps, improve the affinity of the two, and make the dispersion more uniform; The silica microspheres are modified hollow mesoporous silica. Pentaerythritol triacrylate is first anchored into the cavity of the hollow mesoporous silica, and then 2,2,3,3,3-pentafluoropropyl acrylate, 2-vinylbenzimidazole and pentaerythritol triacrylate are introduced to obtain a longer chain and improve the hydrophobicity. 2,2,3,3,3-pentafluoropropyl acrylate can reduce the surface energy and improve the hydrophobicity. Vinylbenzimidazole has corrosion resistance and good bonding with the metal matrix. Pentaerythritol triacrylate can increase the branched structure and improve the film-forming performance. The amount of pentaerythritol triacrylate added should not be too much, and too much branched structure may lead to problems such as decreased compatibility. The silica microspheres contain double bonds. After being sprayed on the surface of electronic products, under the action of a catalyst, addition reaction occurs with the silicon hydrogen group in the organic-inorganic hybrid nano resin, which, on the one hand, increases the crosslinking degree, further improves the hydrophobicity and corrosion resistance, and on the other hand, strengthens the bonding with the surface of the electronic product. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] The following parts are by mass unless otherwise specified; Example 1: S1: Take 28 parts of vinyl trimethoxysilane and 50 parts of vinyl terminated silicone oil with a viscosity of 750 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 55°C, take 25 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 75°C, react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 10 parts of a composite modifier, 5 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:1.5; S3: Take 12 parts of hollow mesoporous silica and 1 part of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.5 parts of 2-vinylbenzimidazole, 0.2 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 12 parts of organic-inorganic hybrid nano resin, 2 parts of silica microspheres, 0.4 parts of silica, 1 part of isopropanol, 60 parts of water, and 0.005 parts of platinum catalyst; stir at a high speed of 1300r / min for 25min to obtain a nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain a waterproof material.

[0016] Example 2: S1: Take 20 parts of vinyl trimethoxysilane and 40 parts of vinyl terminated silicone oil with a viscosity of 750 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 55°C, take 20 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 75°C, react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 8 parts of a composite modifier, 4 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:1; S3: Take 10 parts of hollow mesoporous silica and 1 part of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.5 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.4 parts of 2-vinylbenzimidazole, 0.2 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 10 parts of organic-inorganic hybrid nano resin, 2 parts of silica microspheres, 0.5 parts of silica, 2 parts of isopropanol, 58 parts of water, and 0.005 parts of platinum catalyst; stir at 1300r / min for 25min to obtain nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain waterproof material.

[0017] Example 3: S1: Take 30 parts of vinyl trimethoxysilane and 50 parts of vinyl terminated silicone oil with a viscosity of 750 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 60°C, take 30 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 70°C, react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 10 parts of a composite modifier, 6 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:2; S3: Take 15 parts of hollow mesoporous silica and 2 parts of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.6 parts of 2-vinylbenzimidazole, 0.3 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 15 parts of organic-inorganic hybrid nano resin, 1 part of silica microspheres, 0.3 parts of silica, 2 parts of isopropanol, 60 parts of water, and 0.005 parts of platinum catalyst; stir at a high speed of 1300r / min for 25min to obtain a nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain a waterproof material.

[0018] Comparative Example 1 (increasing the viscosity of the vinyl-terminated silicone oil, the remaining method steps are consistent with Example 1): S1: Take 28 parts of vinyl trimethoxysilane and 50 parts of vinyl-terminated silicone oil with a viscosity of 2000 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 55°C, take 25 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 75°C, react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 10 parts of a composite modifier, 5 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:1.5; S3: Take 12 parts of hollow mesoporous silica and 1 part of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.5 parts of 2-vinylbenzimidazole, 0.2 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 12 parts of organic-inorganic hybrid nano resin, 2 parts of silica microspheres, 0.4 parts of silica, 1 part of isopropanol, 60 parts of water, and 0.005 parts of platinum catalyst; stir at a high speed of 1300r / min for 25min to obtain a nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain a waterproof material.

[0019] Comparative Example 2 (reducing the viscosity of the vinyl-terminated silicone oil, the remaining method steps are consistent with Example 1): S1: Take 28 parts of vinyl trimethoxysilane and 50 parts of vinyl-terminated silicone oil with a viscosity of 400 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 55°C, take 25 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 75°C, react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 10 parts of a composite modifier, 5 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:1.5; S3: Take 12 parts of hollow mesoporous silica and 1 part of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.5 parts of 2-vinylbenzimidazole, 0.2 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 12 parts of organic-inorganic hybrid nano resin, 2 parts of silica microspheres, 0.4 parts of silica, 1 part of isopropanol, 60 parts of water, and 0.005 parts of platinum catalyst; stir at a high speed of 1300r / min for 25min to obtain a nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain a waterproof material.

[0020] Comparative Example 3 (increasing the amount of pentaerythritol triacrylate B added, and the remaining steps are consistent with Example 1): S1: Take 28 parts of vinyl trimethoxysilane and 50 parts of vinyl-terminated silicone oil with a viscosity of 750 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 55° C., take 25 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 75° C., react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 10 parts of a composite modifier, 5 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:1.5; S3: Take 12 parts of hollow mesoporous silica and 1 part of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.5 parts of 2-vinylbenzimidazole, 0.4 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 12 parts of organic-inorganic hybrid nano resin, 2 parts of silica microspheres, 0.4 parts of silica, 1 part of isopropanol, 60 parts of water, and 0.005 parts of platinum catalyst; stir at a high speed of 1300r / min for 25min to obtain a nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain a waterproof material.

[0021] Comparative Example 4 (no platinum catalyst is added to the nano coating, and the remaining steps are consistent with Example 1): S1: Take 28 parts of vinyl trimethoxy silane and 50 parts of vinyl terminated silicone oil with a viscosity of 750 cSt, dilute them with a mixed solvent to a mass concentration of 50%, add 10 ppm of platinum catalyst under nitrogen protection, heat to 55°C, take 25 parts of tetramethylcyclotetrasiloxane, dilute it with cyclohexane to a mass concentration of 50%, drop it, heat to 75°C, react for 3 hours, remove the solvent, and obtain a tackifier; S2: Under the protection of nitrogen, 10 parts of a composite modifier, 5 parts of silica sol, and 100 parts of water are mixed, the temperature is raised to 80° C., 0.6 parts of 1M nitric acid as a catalyst is added, and the mixture is kept warm for 8 hours before discharging the mixture to obtain an organic-inorganic hybrid nano-resin; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a mass ratio of 1:1.5; S3: Take 12 parts of hollow mesoporous silica and 1 part of pentaerythritol triacrylate A, add them to 400 parts of ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 3 hours, add 0.3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.5 parts of 2-vinylbenzimidazole, 0.2 parts of pentaerythritol triacrylate B, and 0.01 parts of BPO, stir at 78°C for 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres; S4: Take 12 parts of organic-inorganic hybrid nano resin, 2 parts of silica microspheres, 0.4 parts of silica, 1 part of isopropanol, and 60 parts of water; stir at a high speed of 1300r / min for 25 minutes to obtain a nano coating; spray it on the surface of electronic products with a spraying thickness of 1μm, bake at 75℃ for 2h, and dry to obtain a waterproof material.

[0022] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: vinyl trimethoxysilane (CAS: 2768-02-7); vinyl terminated silicone oil (Rongli single-end vinyl terminated dimethyl silicone oil, viscosity customized, Zhejiang Rongli High-tech Materials Co., Ltd.); platinum catalyst (Article No.: 8598479, Wuhan Kanos Technology Co., Ltd.); tetramethylcyclotetrasiloxane (CAS: 2370-88-9); cyclohexane (CAS: 110-82-7); toluene (CAS: 108-88-3); silica sol (CG210, Shandong Zhengxing New Materials Co., Ltd.); cyclohexane (CAS: 110-82-7); toluene (CAS: 108-88-3); silica sol (CG210, Shandong Zhengxing New Materials Co., Ltd.); Oxysilane coupling agent (CAS: 2530-83-8); hollow mesoporous silica (YM-NM-021, Changsha Yimo Biotechnology Co., Ltd.); pentaerythritol triacrylate A, pentaerythritol triacrylate B (pentaerythritol triacrylate, CAS: 3524-68-3); ethanol (CAS: 64-17-5); 2,2,3,3,3-pentafluoropropyl acrylate (CAS: 356-86-5); 2-vinylbenzimidazole (CAS: 14984-26-0); BPO (CAS: 94-36-0); silica (YM-SiO2-50, Yumu Ningbo New Materials Co., Ltd.); isopropyl alcohol (CAS: 67-63-0).

[0023] Experiment: Take the nano coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 4, spray them on the surface of the copper substrate with a spraying thickness of 1 μm, bake at 75° C. for 2 h, and dry to obtain samples; (1) test the hydrophobic angle; (2) test the corrosion potential; see the table below for specific data; Conclusion: Comparative Examples 1 and 2 changed the viscosity of the vinyl-terminated silicone oil, both resulting in a decrease in performance, which shows that viscosity is of great significance; Comparative Example 3 increased the amount of pentaerythritol triacrylate B added, resulting in excessive branching structure, affecting the final performance; Comparative Example 4 did not add a platinum catalyst to the nano-coating, the interaction between the organic-inorganic hybrid nano-resin and the silica microspheres was weakened, and the performance decreased; In summary, the nano-coating prepared by the present invention has good waterproof and corrosion resistance, and can be sprayed on the surface of electronic products to obtain a waterproof material with excellent performance.

[0024] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a waterproof material for electronic products, characterized in that: The following steps are involved: S1: Mix the composite modifier, silica sol and water under nitrogen protection, heat to 75-80°C, add nitric acid, keep warm for 6-8h, and discharge to obtain organic-inorganic hybrid nano resin; S2: Take organic-inorganic hybrid nano resin, silica microspheres, silica, isopropanol, water, and platinum catalyst, stir at high speed to obtain nano coating; spray the nano coating onto the surface of the electronic product, bake at 70-80° C. for 2-3 hours, and dry to obtain a waterproof material.

2. The method for preparing a waterproof material for electronic products according to claim 1, characterized in that: The organic-inorganic hybrid nano resin comprises the following raw materials, calculated by weight: 8-10 parts of a composite modifier, 4-6 parts of silica sol, 80-100 parts of water, and 0.5-0.8 parts of 1M nitric acid; the composite modifier comprises an epoxy silane coupling agent and a tackifier in a weight ratio of 1:(1-2).

3. The method for preparing a waterproof material for electronic products according to claim 2, characterized in that: The preparation of the tackifier comprises the following steps: Take vinyltrimethoxysilane and vinyl-terminated silicone oil, dilute them, add platinum catalyst under nitrogen protection, heat to 50-60°C, add diluted tetramethylcyclotetrasiloxane dropwise, heat to 70-75°C, react for 2-3 hours, remove the solvent, and obtain a tackifier.

4. The method for preparing a waterproof material for electronic products according to claim 3, characterized in that: The tackifier comprises the following raw materials, calculated by weight: 20 to 30 parts of vinyl trimethoxy silane, 40 to 50 parts of vinyl terminated silicone oil, and 20 to 30 parts of tetramethyl cyclotetrasiloxane.

5. The method for preparing a waterproof material for electronic products according to claim 4, characterized in that: The viscosity of the vinyl terminated silicone oil is 500-1000 cSt.

6. The method for preparing a waterproof material for electronic products according to claim 1, characterized in that: The preparation of the silica microspheres comprises the following steps: Take hollow mesoporous silica and pentaerythritol triacrylate A, add them to ethanol and stir evenly, place them in a vacuum box with a pressure of -50 kPa for 2 to 3 hours, add 2,2,3,3,3-pentafluoropropyl acrylate, 2-vinylbenzimidazole, pentaerythritol triacrylate B, and dibenzoyl peroxide, stir at 75 to 78 ° C for 10 to 12 hours under nitrogen protection, remove the solvent, and obtain silica microspheres.

7. The method for preparing a waterproof material for electronic products according to claim 6, characterized in that: The silica microspheres include the following raw materials, calculated by weight: 10-15 parts of hollow mesoporous silica, 1-2 parts of pentaerythritol triacrylate A, 300-400 parts of ethanol, 0.3-0.5 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 0.4-0.6 parts of 2-vinylbenzimidazole, 0.2-0.3 parts of pentaerythritol triacrylate B, and 0.01-0.02 parts of dibenzoyl peroxide.

8. The method for preparing a waterproof material for electronic products according to claim 1, characterized in that: The nano coating comprises the following raw materials, calculated by weight: 10-15 parts of organic-inorganic hybrid nano resin, 1-2 parts of silicon dioxide microspheres, 0.3-0.5 parts of silicon dioxide, 1-2 parts of isopropanol, 55-60 parts of water, and 0.005-0.006 parts of platinum catalyst.

9. The method for preparing a waterproof material for electronic products according to claim 1, characterized in that: The nano coating spray thickness is 1~2μm.

10. A waterproof material prepared according to the method for preparing a waterproof material for electronic products according to any one of claims 1 to 9.